SUSTAINABLE FINANCE AND ITS ROLE IN PROMOTING DEVELOPMENT IN DEVELOPING COUNTRIES - Amina Khettabet,; Hocine Elamine Cheriet,; Hakim Hallab, (International Journal of Innovative Technologies in Social Science, 2025)
This article presents an analytical study on the role of sustainable finance in achieving the Sustainable Development Goals (SDGs), with a particular focus on developing countries. It begins with a central problem: the limited effectiveness of traditional financing in addressing environmental and social challenges. Sustainable finance is thus highlighted as a strategic alternative that combines economic efficiency with social and environmental responsibility. Following a conceptual framework and an overview of global and regional challenges, the study examines successful comparative experiences, such as those of the European Union and China, in order to identify factors of success and areas of failure. The article emphasizes the importance of legal and institutional reforms in enabling developing countries to benefit from sustainable finance, and concludes with a set of recommendations to develop efficient, integrated, and context-appropriate models of sustainable finance.